Conflict - Sidaway, Ashley; Sidaway, Robert; Sellar, Maurice; Mills, John, Sir (Herts: Screen Entertainment, 1991)
Conflict shows British films have always been at their best when looking at intimate relationships and how individuals cope within our complex modern society. Through the 50's and 60's world audiences learned to respect the integrity and skill of some of our finest writers and directors with films that looked at the world of conflict at work, home and at play, with insight, honesty and compassion
Rebel shows how British film-makers have dealt with the way the individual rebels and shows some of the superb box office successes
Rebel
Narrated by John Mills
Keywords: Alienation (Social psychology) in motion pictures; Interpersonal conflict -- Drama; Motion pictures -- United Kingdom -- History